Volatilization of mercury in coal during conventional and microwave drying and its potential guidance for environmental protection. (1st March 2018) - Zhang, Ningning; Zhou, Changchun; Xia, Wencheng; Nguyen, Anh V.
Abstract: During the thermal drying process of coal, the sufficient attention has been paid to the changes in the properties of coal before and after the drying process. However, the volatility characteristics of harmful trace elements in coal during the drying process are always neglected to date, whereas the volatilization of harmful trace elements not only has significant effects on the surrounding atmosphere environment but also influence the following utilization of dried coal. In this study, the volatility characteristics of both the moisture and mercury in the coal sample during conventional (electric blast oven) and microwave (microwave oven) drying processes were investigated. In addition, the changes in the surface properties of coal before and after the drying process were studied using X-ray photoelectron spectroscopy (XPS) analysis. The results show that the moisture content of coal decreases in non-line format (decreases slowly at the first and then quickly according to the drying time) in the conventional drying process, while it decreases in line format in the microwave drying. The microwave drying process needs much shorter time required to obtain the dried coal of a certain moisture content than the conventional drying process. Under the same volatilization rate of moisture, the volatilization rate of mercury in the microwave drying process is always greater than that in the conventional drying process. Nearly half or more (49.73% and 59.26%, respectively) of the mercury in the coal slime evaporates into the atmosphere after the drying processes. XPS results show the content of CC and CH groups on the coal surface increased, but the CO content decreased after the drying processes and the microwave drying process has a stronger ability to remove oxygen-containing functional groups than the conventional drying process. Highlights: Volatilization of mercury during coal drying was investigated. Half of the mercury evaporated during the drying of coal. More mercury evaporated in microwave drying than in conventional drying.